2007
DOI: 10.1093/humrep/del490
|View full text |Cite
|
Sign up to set email alerts
|

Sperm quality and pregnancy rate after COX-2 inhibitor therapy of infertile males with abacterial leukocytospermia

Abstract: Our results suggest that a decrease in leukocytospermia after rofecoxib therapy was associated with recovery of all seminal characteristics in basal and swim-up selected samples. This general improvement could justify the positive outcome of ART after anti-inflammatory therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 23 publications
1
50
0
2
Order By: Relevance
“…It has been demonstrated that inhibitors of COX-2 have a positive effect on sperm quality, associated with an increase in the volume of the ejaculate in humans (Gambera et al, 2007). This would be useful in further studies to evaluate the security of non-steroidal anti-inflammatory drugs in the testes of animals exposed to boron.…”
Section: Morphometric and Histopathological Analysismentioning
confidence: 96%
“…It has been demonstrated that inhibitors of COX-2 have a positive effect on sperm quality, associated with an increase in the volume of the ejaculate in humans (Gambera et al, 2007). This would be useful in further studies to evaluate the security of non-steroidal anti-inflammatory drugs in the testes of animals exposed to boron.…”
Section: Morphometric and Histopathological Analysismentioning
confidence: 96%
“…In one study men with antibiotic treated Chlamydia or Ureaplasma infection were randomized to either a NSAID or carnitine antioxidant and monitored for improvements in sperm quality over the next 4 months [151]. In addition, a one month course of a COX-2 anti-inflammatory along with 2 months of carnitine has been shown to significantly reduce sperm leukocyte count, while improving sperm motility, morphology and viability [152].…”
Section: Treating Infectionsmentioning
confidence: 99%
“…The demonstration of an association between increased seminal leukocyte concentrations and decreased male fertility has led to the investigation of therapeutic strategies for leukocytospermia (5,11,16,17). Studies have shown that reducing leukocyte concentrations can help improve other semen parameters, such as sperm concentration, motility, and morphology (11,16,17).…”
mentioning
confidence: 99%
“…Studies have shown that reducing leukocyte concentrations can help improve other semen parameters, such as sperm concentration, motility, and morphology (11,16,17). However, most of these studies were not placebo controlled and therefore did not provide data on spontaneous improvement of, or remission rates for, leukocytospermia in the absence of treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation